A normal abundance of faint satellites in the fossil group NGC 6482 - Lieder, Stefan; Mieske, S.; Sánchez-Janssen, R.; Hilker, M.; Lisker, Thorsten; Tanaka, M. (Astronomy and astrophysics, 2013)
A fossil group is considered the end product in a galaxy group’s evolution. It is a massive central galaxy that dominates the luminosity budget of the group, and is the outcome of efficient merging between intermediate-luminosity members. Little is known, however, about the faint satellite systems of fossil groups. Here we present a Subaru/Suprime-Cam wide-field, deep imaging study in the B− and R−bands of the nearest fossil group NGC 6482 (Mtot ~ 4 × 1012 M⊙), covering the virial radius out to 310 kpc. We performed detailed completeness estimations and selected group member candidates by a combination of automated object detection and visual inspection. A fiducial sample of 48 member candidates down to MR ~ −10.5 mag is detected, making this study the deepest of a fossil group to now. We investigate the photometric scaling relations, the color-magnitude relation, and the luminosity function of our galaxy sample. We find evidence of recent and ongoing merger events among bright group galaxies. The color-magnitude relation is comparable to that of nearby galaxy clusters, and it exhibits significant scatter at the faintest luminosities. The completeness-corrected luminosity function is dominated by early-type dwarfs and is characterized by a faint end slope α = −1.32 ± 0.05. We conclude that the NGC 6482 fossil group shows photometric properties consistent with those of regular galaxy clusters and groups, including a normal abundance of faint satellites.